The August 1st, 2014 (Mw 5.3) Moderate Earthquake: Evidence for an Active Thrust Fault in the Bay of Algiers (Algeria) - Benfedda, Amar (2018)
On August 1st, 2014, a moderate-sized earthquake struck the capital city of Algiers at 05:11:17.6 (GMT+1). The earthquake caused the death of six peoples and injured 420, mainly following a panic movement among the population. Following the main shock, we surveyed the aftershock activity using a portable seismological network (short period), installed from August 2nd, 2014 to August 21st, 2015. In this work, first, we determined the main shock epicenter using the accelerograms recorded by the Algerian accelerograph network (under the coordination of the National Center of Applied Research in Earthquake Engineering–CGS). We calculated the focal mechanism of the main shock, using the inversion of the accelerograph waveforms in displacement that provides a reverse fault with a slight right-lateral component of slip and a compression axis striking NNW–SSE. The obtained scalar seismic moment (M o = 1.25 × 1017 Nm) corresponds to a moment magnitude of M w = 5.3. Second, the analysis of the obtained aftershock swarm, of the survey, suggests an offshore ENE–WSW, trending and NNW dipping, causative active fault in the bay of Algiers, which may likely correspond to an offshore unknown segment of the Sahel active fault.